Concert by the Band of the Antifascist Militias organized by the "Oficina de propaganda" of the CNT on the Plaza de Cataluña. Toryho: in the centre, with glasses. Series of 2 photos. Copied from CNT collection
Concert by the Band of the Antifascist Militias organized by the "Oficina de propaganda" of the CNT on the Plaza de Cataluña. Toryho: in the centre, with glasses. Series of 2 photos. Copied from CNT collection.